The Isfahan Comprehensive Elderly Study: Objectives, research design, methodology, and preliminary results - Heidari, Zahra (J Res Med Sci, 2017)
BACKGROUND: This paper presents the objectives, research design, methodology, and primary findings of the Isfahan Comprehensive Elderly Study (ICES). MATERIALS AND METHODS: In this cross-sectional study, 603 elderly persons (aged 60 and over) were selected by multistage cluster sampling method from Isfahan, Iran, in 2016 comprehensive questionnaires along with a detailed interview were used to collect information on personal, family, socioeconomic, health and social services characteristics, life styles, physical illnesses and chronic diseases, mental, emotional and cognition disorders, quality of life, disabilities, sleep quality, social supports, life satisfaction, self-efficacy, and of participants. RESULTS: The mean ± standard deviation (SD) age of participants was 69.66 ± 6.31 years, consisting of 50.75% females. About 23% of elderly persons were at the risk of malnutrition and 4.5% were current smoker. Severe and mild depression were documented in 9.3% and 30.2% among included study subjects, respectively. About half of the participants had hypertension, and 26.8% suffered from cardiovascular disease. The mean ± SD of total score of Geriatric Depression Scale, Perceived Stress Scale, Older People's Quality of Life, Physical Activity Scale for the Elderly and Pittsburg Sleep Quality Index was 8.84 ± 6.79, 14.76 ± 5.92, 133.99 ± 10.55, 142.04 ± 120.53, and 6.17 ± 3.44, respectively. Elderly males had significantly higher life satisfaction and self-efficacy and better cognitive function than females (P < 0.01). CONCLUSION: The findings of current study provided a comprehensive overview of the current health status and lifestyle of older adults in Isfahan city. The ICES could help policy makers to design appropriate prevention and interventional programs and policies to cover the specific needs of the elderly population.